Voice and advocate of youth National Youth Commission Davao brochure design template : a print production thesis - Gomez, Maries P.
This print production thesis created a brochure design template for the National Youth Commission Davao (NYC) that directly communicates to the youth of Region XI, the NYC programs for youth development. The brochure was designed to contain relevant information about NYC Davao and their frontline coordinated programs for the youth in the area contrariwise to the existing print materials created by NYC National that have broad and irrelevant information. The researcher conducted research, analyzed the existing NYC print materials and gathered needed information that became the basis for the design of the NYC Davao Brochure. The researcher created five leaflets for each program of NYC which were inserted in the jacket brochure. The researcher also included registration forms to encourage action from the target audience. To achieve the youthful and dynamic concept, the researcher applied die-cutting and principles of design in selecting and arranging the typographic and pictographic elements in the brochure. The brochure helps NYC Davao inform the youth in the area about programs that leads to youth development. This can encourage the youth to register with NYC and encourage them to participate in the said programs.